Applications and Pitfalls of Endoscopy in Inflammatory Bowel Disease. (1st November 1990) - Salena, BJ; Hunt, RH
Abstract : The role of upper gastrointestinal and hepatobiliary endoscopy and colonoscopy in the diagnosis and management of patients with inflammatory bowel disease (IBD) is reviewed. The differentiation of IBD from other forms of colitis, mass lesions in the colon, strictures and polyps, and the management of the patient with dysplasia including clinical strategies for early detection are discussed. The role and value of endoscopic surveillance programs have yet to be defined.